Educational and Behavioral Disparities among Kindergarten Children and their Peers Who did not enroll in it from the Point of View of the First Grade Teachers in the Light of Some Variables - Khalid, Mohammed Ali Bani (International Journal of Educational Studies, 2019)
This study aims to know the educational and behavioral differences between kindergarten children and their friends who did not enrolled in kindergarten from point of view of first grade teachers, the total sample of the study consist of 58 first grade teachers. to achieve the goals of the study the analytical descriptive approach has been used, tool of the study has been developed by the researcher consisting 43 items distributed into four areas were checked by specialist professors. Results indicated that there are educational and behavioral differences in favor of the students who attend the kindergarten, which is presents the important of kindergarten stage.